2016
DOI: 10.1093/nar/gkw756
|View full text |Cite
|
Sign up to set email alerts
|

Stable nuclear expression ofATP8andATP6genes rescues a mtDNA Complex Vnullmutant

Abstract: We explore the possibility of re-engineering mitochondrial genes and expressing them from the nucleus as an approach to rescue defects arising from mitochondrial DNA mutations. We have used a patient cybrid cell line with a single point mutation in the overlap region of the ATP8 and ATP6 genes of the human mitochondrial genome. These cells are null for the ATP8 protein, have significantly lowered ATP6 protein levels and no Complex V function. Nuclear expression of only the ATP8 gene with the ATP5G1 mitochondri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 56 publications
1
28
0
Order By: Relevance
“…In addition to plants, allotopic expression of mitochondrial genes in the nucleus was proposed as a potential method for gene therapy [30]. Recently, stable nuclear expression of ATP8 and ATP6 genes was shown to rescue a Complex V null mutant derived from a patient cybrid cell line carrying a mutation in the human mitochondrial genome [31]. Thus far, nad7 is the only mitochondrial gene reported to be successfully expressed in the nucleus in plants.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to plants, allotopic expression of mitochondrial genes in the nucleus was proposed as a potential method for gene therapy [30]. Recently, stable nuclear expression of ATP8 and ATP6 genes was shown to rescue a Complex V null mutant derived from a patient cybrid cell line carrying a mutation in the human mitochondrial genome [31]. Thus far, nad7 is the only mitochondrial gene reported to be successfully expressed in the nucleus in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown an association between breast cancer and mutations on ATP6 and ATP8 genes that encode the a-subunit of the F 1 Fo ATP synthase [ 114 , 115 , 116 ]. The a-subunit is critical in the rotation of F 1 Fo ATP synthase, a necessary process during ATP production; therefore, ATP6 and ATP8 mutations negatively influence mitochondrial energy metabolism [ 117 ]. In addition to mutation, breast cancer pathology alters the abundance of other subunits of the F 1 Fo ATP synthase [ 118 ].…”
Section: Alteration Of Mitochondrial Energy Metabolismmentioning
confidence: 99%
“…Of these 6 up-regulated proteins, vacuolar-type H-ATPase subunit E (ATP6E) belong to superfamily of related ATP synthases. Co-expression of ATP8 and ATP6 genes provided stable protein expression for complex V assemble of the oxidative phosphorylation complexes (Boominathan et al 2016). The upregulation of V-ATPase gene (ATP6V0D2) was found in the zone of hypertrophic chondrocytes, which was part of the process of endochondral ossification (Ayodele et al 2017).…”
Section: Kegg Annotation Of Differentially Expressed Proteinsmentioning
confidence: 99%